Economic appraisal of the public control and prevention strategy against the 2010 West Nile Virus outbreak in Central Macedonia, Greece. (February 2016) - Kolimenakis, A.; Bithas, K.; Richardson, C.; Latinopoulos, D.; Baka, A.; Vakali, A.; Hadjichristodoulou, C.; Mourelatos, S.; Kalaitzopoulou, S.; Gewehr, S.; Michaelakis, A.; Koliopoulos, G.
Abstract: Objectives: The aim of the present paper is to evaluate the economic efficiency of the public control and prevention strategies to tackle the 2010 West Nile Virus (WNV) outbreak in the Region of Central Macedonia, Greece. Efficiency is examined on the basis of the public prevention costs incurred and their potential in justifying the costs arising from health and nuisance impacts in the succeeding years. Study design: Economic appraisal of public health management interventions. Methods: Prevention and control cost categories including control programmes, contingency planning and blood safety testing, are analyzed based on market prices. A separate cost of illness approach is conducted for the estimation of medical costs and productivity losses from 2010 to 2013 and for the calculation of averted health impacts. The averted mosquito nuisance costs to households are estimated on the basis of a contingent valuation study. Based on these findings, a limited cost-benefit analysis is employed in order to evaluate the economic efficiency of these strategies in 2010–2013. Results: Results indicate that cost of illness and prevention costs fell significantly in the years following the 2010 outbreak, also as a result of the epidemic coming under control. According to the contingent valuation survey, the annual average willingness to pay to eliminate the mosquito problem in the study area ranged between 22 and 27 € per household. Cost-benefit analysis indicates that the aggregate benefit of implementing the previous 3-year strategy creates a net socio-economic benefit in 2013. However the spread of the WNV epidemic and the overall socio-economic consequences, had the various costs not been employed, remain unpredictable and extremely difficult to calculate. Conclusions: The application of a post epidemic strategy appears to be of utmost importance for public health safety. An updated well designed survey is needed for a more precise definition of the optimum prevention policies and levels and for the establishment of the various cost/benefit parameters. Highlights: Overall costs in the first years of the epidemic appear higher. Benefit examined on the basis of averted health and nuisance costs in future years. Uncertainty for size of the epidemic and its costs without any prevention measures. Post epidemic strategy highly important mainly in terms of public health safety.